Beyond Coercion: Moral Assessment in the Labour Market - Munter, Dan (Journal of business ethics, 2017)
Some libertarians argue that informed consent alone makes transactions in the labour market morally justified. In contrast, some of their critics claim that such an act of consent is no guarantee against coercion. To know whether agreements are voluntary, we need to assess the quality of the offers or the prevailing background conditions. ISCT theorists argue that it is imperative to take social norms into account when evaluating the labour market. We present a novel framework for moral assessment in the labour market, which takes consent, background conditions and norms into account, but which mainly focuses on the offers and demands made. Consent renders a transaction legitimate in the same way we regard a fair election legitimate even if we object to its outcome. For offers to be substantially justified, exploitation must be avoided and offers must give expression to the value of community. Only then they are morally justified.